2019
DOI: 10.4274/balkanmedj.2018.0922
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-Generation Sequencing of MLH1, MSH2, and MSH6 Genes in Patients with Endometrial Carcinoma under 50 Years of Age

Abstract: This study emphasized that Lynch syndrome should be investigated in patients having EC diagnosed under 50 years of age because of increased lifetime risk for various cancers and this study determined the mutation frequency in MMR genes as the first time in Turkish patients with EC diagnosed <50 years of age by revealing both known and novel variants using NGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…Our study reports a higher mutation rate in the MMR genes (42.1%), compared to other studies (18–22.7%) [ 16 , 20 ]. Particularly, in our cohort of patients, we found no differences in the percentage of pathogenic variants in the analyzed genes, as we revealed a percentage of 50% in both MLH1 and MSH2 .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our study reports a higher mutation rate in the MMR genes (42.1%), compared to other studies (18–22.7%) [ 16 , 20 ]. Particularly, in our cohort of patients, we found no differences in the percentage of pathogenic variants in the analyzed genes, as we revealed a percentage of 50% in both MLH1 and MSH2 .…”
Section: Discussioncontrasting
confidence: 70%
“…Mutational analysis of exons of MLH1 , MSH2 , BRCA1 , BRCA2 and adjacent intronic regions was performed with NGS, as previously described [ 15 , 16 ]. The presence of the pathogenic variant was confirmed on the other blood sample by Sanger sequencing, as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The APC gene has been proposed as a prominent tumor-promoting gene participating in the tumorigenesis of CRC and/or adenomatous polyposis coli. 33 APC pathogenic/likely pathogenic variations were present in 3 cases (3.75%) of colon cancer and familial adenomatous polyposis coli in the present study. Liu and Tan 8 analyzed a 183-gene panel in gastrointestinal cancers and reported that the 7 most frequently mutated genes were MSH2, ATM, FANCD2, ATR, BRCA2, FANCA , and BRCA1.…”
Section: Discussionsupporting
confidence: 53%
“…Endometrial carcinoma is divided into four different molecular subtypes: POLE acculturated; Microsatellite instability hypermutated (MSI-H); Copy number abnormalities-low (CN-L), and Copy number abnormalities-high (CN-H). Literature has reported that MSI exists in many types of solid tumors, such as EC, colorectal cancer, and lung cancer [ 22 ], and is also related to Lynch and sporadic endometrial carcinoma [ 23 ]. In TCGA studies, MSI high mutants accounted for about 30% of EC, 28.6% of low-grade EEC and 54.3% of high-grade EEC belonged to MSI type.…”
Section: Discussionmentioning
confidence: 99%